First principles study of the spin–orbit interaction effect on the opto-electric properties of lead telluride. (January 2016) - Rashid, Bahroz; Hilal, Muhammad; Haider Khan, Shah; Khan, Afzal
Abstract: The first-principles calculations of opto-electric properties of lead telluride (PbTe) were performed for photo-voltaic applications in the infrared, visible and ultraviolet regions. These calculations are based on full potential linearized augmented plane wave method (FP-LAPW) within density functional theory (DFT) implemented by WIEN2k. The results, we are presenting in this paper, are much closer to the experimental values as compared to the other published theoretical data using generalized gradient approximation and modified Becke Johnson approximation for exchange co-relation potential. These results were further refined by adding the potential contribution from spin–orbit interaction (SOI) of electrons. Additional advantage of applying SOI is the k -points independent calculations of the opto-electric properties of PbTe. In addition to other calculated properties, the calculated energy band gap for PbTe is E g = 0.19 eV, the peak value of absorption coefficient 132 × 10 4 cm − 1 at 2.2 eV and the critical points of optical spectra are 1.2 eV, 2.2 eV and 3.2 eV.